Conceptual Model of Factors Affecting Mathematics Literacy Based on the Perspective of 9th Grade Students: A Qualitative Research - Narges Yaftian; Maryam Shayan (رویکردهای نوین آموزشی)
This research was conducted to analyze the factors affecting the mathematical literacy of the 9th grade students. The data were collected with a qualitative approach and the use of semi-structured interviews. The research participants were among the 9th grade students of Isfahan city, who were selected using a purposeful approach and criteria-based sampling. In this research, theoretical saturation was achieved with 15 students. The qualitative data obtained from the interviews were analyzed using the process of open, axial and selective coding. To ensure the quality of the research and validation of the findings, several strategies were used such as continuous interaction with the participants as well as assessment, review and verification of the data by experts. Based on the viewpoint of ninth grade students, the identified categories and subcategories were classified into two general categories of external and internal factors. The internal factors including the subcategories of learning mathematics, math study, motivation, metacognition, problem solving skills and beliefs were classified and the subcategories of society, educational environment and family were placed under the external factors affecting the mathematical literacy of the 9th grade students. Finally, as a general finding of the research, the conceptual model of factors affecting students' mathematical literacy was formulated and presented. IntroductionIn the domain of student education, mathematical literacy has emerged as one of the fundamental competencies that has garnered international attention and become a subject of global discourse. In most educational systems, mathematical literacy is the ability to solve real-world problems using school mathematics (Ojose, 2011). Researchers have emphasized that possessing this skill is a tool for strengthening other 21st-century skills (Wulandari & Azka, 2018; Tanujaya et al., 2021; Abidin et al., 2021; Hidayati et al., 2020).Since 2000, the Program for International Student Assessment (PISA), organized by the Organization for Economic Co-operation and Development (OECD), has been conducting tests to evaluate the mathematical, scientific, and reading literacy of 15-year-old students. The OECD defines mathematical literacy as an individual's ability to formulate, employ, and interpret mathematics in diverse contexts. This includes mathematical reasoning and the use of mathematical concepts, methods, facts, and tools to describe, explain, and predict phenomena (OECD, 2017; 2019; 2023).Published reports on the results of PISA mathematical literacy assessments have prompted some researchers to conduct studies on factors influencing students' mathematical literacy. Findings from several studies indicate that in the domain of student education, factors such as academic skills and motivation (Cleary & Kitsantas 2017; Kitsantas et al. 2021), textbook content (Dewantara, 2020; Pakpahan, 2017; Suharyono & Rosnawati, 2020), mathematical interest and self-concept (Chu et al., 2016; Brown  & Stillman, 2017; Holenstein et al., 2021), gender (Magen-Nagar, 2016), teaching methods (Retnawati et al., 2018; OECD, 2013b; Fauzan, & Arnawa, 2020; Wentzel et al., 2017), teachers’ behavior (Magen-Nagar, 2016), emotional support from teachers (Wentzel et al., 2017), and school type and the facilities (Kartianom & Ndayizeye, 2017) impact students' mathematical literacy levels.A review of existing national and international research on mathematical literacy reveals that numerous studies, primarily using quantitative approaches, have been conducted internationally to assess mathematical literacy and the factors influencing it at schools and universities. Iran's contribution to this research has been limited. Notably, no studies were found that examined factors affecting mathematical literacy from the students' perspectives. In light of contemporary global transformations and the emphasis placed by international communities on students' mathematical literacy skills, it is crucial to take proactive steps toward enhancing mathematical literacy. The present study, employing a qualitative approach, aimed to address this main research question: "What factors exert influence on mathematical literacy from the perspective of ninth-grade students?" Research Methodology The present study employed a qualitative approach, with data analyzed using open, axial, and selective coding methods. Participants were selected from among ninth-grade students in Isfahan city. A purposive sampling approach with criterion-based selection was utilized to choose research participants. Accordingly, students who were interested and active in solving challenging mathematical problems were selected to provide maximum rich information. Data were collected through in-depth semi-structured interviews, with theoretical saturation achieved after interviewing 15 students. The main framework of the interview questions revolved around exploring factors influencing the mathematical literacy of ninth-grade students.Findings Based on the perspectives of ninth-grade students, the identified categories and subcategories were classified into two main groups: external and internal factors. Internal factors encompass subcategories such as learning mathematics, studying mathematics, motivation, meta-cognition, problem-solving skills, and beliefs. Each of these subcategories further comprised subcategories. For instance, the subcategory of beliefs included subcategories such as the importance of mathematics, the tangibility of mathematics, the value of learning mathematics, the need for intelligence in learning mathematics, the applicability of mathematics, and internal feelings towards mathematics. Similarly, the subcategory of problem-solving included subcategories like attitude towards problem-solving, problem formulation, use of problem-solving methods, backtracking, and the ability to understand problems.External factors influencing ninth-grade students' mathematical literacy included subcategories of society, educational environment, and family. The research findings indicated that each of these subcategories also contained subcategories. For example, the subcategory of society encompassed secondary categories such as teachers, classmates, mathematics examinations, school, textbook content, and school environment. As a comprehensive finding of the study, a conceptual model of factors influencing students' mathematical literacy was developed and presented. Discussion and Conclusion Based on the findings, the value and status of mathematics in society and the impact of mathematical learning on learners' personalities were factors categorized under the societal category. The extent of parental involvement in monitoring their children's mathematical skills and the parents' educational levels were identified as influential family factors. The categories of society, educational environment, and family were recognized as external factors affecting ninth-grade students' mathematical literacy. A notable aspect of the findings is the identification of categories not previously found in global research. The value and status of mathematics in Iranian society and parental monitoring of children's mathematical skills, as subcategories of society and family respectively, are examples of such unique findings. It appears that the intense focus of Iranian families on students' success in the national university entrance exam (Konkur) leads to increased emphasis of families on monitoring their children's mathematics learning. In a society like Iran, where higher education is highly valued, such findings are not unexpected. The results suggest that strategies to enhance mathematical literacy should consider not only pedagogical approaches but also broader societal and familial factors. Future research could explore how these unique cultural and social aspects influence mathematical literacy development and how they might be leveraged to improve educational outcomes.